Highly active metal-free carbon dots/g-C3N4 hollow porous nanospheres for solar-light-driven PPCPs remediation: Mechanism insights, kinetics and effects of natural water matrices. (1st April 2020) - Wu, Yuliang; Wang, Fengliang; Jin, Xiaoyu; Zheng, Xiaoshan; Wang, Yingfei; Wei, Dandan; Zhang, Qianxin; Feng, Yiping; Xie, Zhijie; Chen, Ping; Liu, Haijin; Liu, Guoguang
Abstract: Pharmaceuticals and personal care products (PPCPs) are increasingly being scrutinized by the scientific community due to their environmental persistence. Therefore, the development of novel environmentally compatible and energy-efficient technologies for their removal is highly anticipated. In this work, a novel metal-free photocatalytic nanoreactor was successfully synthesized by anchoring carbon dots to hollow carbon nitride nanospheres (HCNS/CDs). The unique structure of these hollow nanospherical HCNS/CDs hybrids endowed them with a high population of reactive sites, while enhancing optical absorption due to internal light reflection. Simultaneously, the CDs served as "artificial antennas" to absorb and convert photons with low energy, due to their superior up-converting properties. Consequently, the HCNS/CDs demonstrated excellent photodegradation activities for the degradation of PPCPs under broad-spectrum irradiation. Remarkedly, 10 mg/L of naproxen (NPX) was completely degraded following 5 min of natural solar irradiation. It was further revealed that the O2 - played a significant role during the photocatalytic process, which could lead to the decomposition of NPX. The effects of natural water matrices and the degradation of trace PPCPs further supported that this photocatalytic system may be efficaciously applied for the remediation of PPCPs contamination in ambient waterways. Graphical abstract: Image 1 Highlights: Carbon dots decorated hollow porous carbon nitride nanosphere was synthesized. The hollow porous structures provided a high population of active sites. The photocatalyst demonstrated remarkable degradation activity. Effects of natural water constituents and water matrices were further investigated.